Cardiac regeneration: Options for repairing the injured heart - Wang, Jun; An, Meilin; Haubner, Bernhard Johannes; Penninger, Josef M. (Frontiers in Cardiovascular Medicine, 2023)
Cardiac regeneration is one of the grand challenges in repairing injured human hearts. Numerous studies of signaling pathways and metabolism on cardiac development and disease pave the way for endogenous cardiomyocyte regeneration. New drug delivery approaches, high-throughput screening, as well as novel therapeutic compounds combined with gene editing will facilitate the development of potential cell-free therapeutics. In parallel, progress has been made in the field of cell-based therapies. Transplantation of human pluripotent stem cell (hPSC)-derived cardiomyocytes (hPSC-CMs) can partially rescue the myocardial defects caused by cardiomyocyte loss in large animals. In this review, we summarize current cell-based and cell-free regenerative therapies, discuss the importance of cardiomyocyte maturation in cardiac regenerative medicine, and envision new ways of regeneration for the injured heart.